Upregulation and hypomethylation of EGFR in Formalin-fixed Paraffin Embedded FFPE tissues of colon adenocarcinoma - Othman, Rosfayati; Mohtaruddin, Norhafizah; Ahmad Zubir, Nurul Mahirah; Seow, Heng Fong; Ngan, Kah Wai; Osman, Malina (Faculty of Medicine and Health Science, Universiti Putra Malaysia, 2021)
Introduction: Colorectal cancer (CRC) is the third most common cancer worldwide. Even though many cancer therapies have been developed, considerable proportions of patients respond poorly to therapy and the number of resistance cases increases. CRC emerges as a result of genetic and/or epigenetic modifications of epidermal growth factor receptor (EGFR) in colonic epithelial cells during tumourigenesis. Determination of DNA methylation status of EGFR is very crucial to further understand the role of this gene in carcinogenesis. However, the applicability of formalin-fixed paraffin embedded (FFPE) tissues in molecular studies is still limited due to high degradation of the nucleic acids. Hence, this study aimed to determine the gene expression and DNA methylation status of EGFR in FFPE CRC samples. Methods: Fifty-nine of archival FFPE CRC cases with the adjacent normal colon tissues were retrieved. Manual micro-dissection was performed prior to RNA and DNA extraction. EGFR expression and DNA methylation status was evaluated by qPCR and methylation specific PCR (MSP) techniques respectively. Results: EGFR was overexpressed in 54.2% (p-value=0.021) of CRC cases. Hypomethylation of EGFR was discovered in 81.4% and 79.7% of FFPE CRC tissues and normal adjacent tissues respectively. No significant association was found between DNA methylation and mRNA levels of EGFR. Conclusion: Determination of gene expression and DNA methylation in FFPE tissues were successfully carried out. The overexpression and hypomethylation of EGFR strongly suggest its important role in CRC tumourigenesis. Hypomethylation in normal tissue adjacent to the tumours indicates this epigenetic change occurs at the early step in carcinogenesis.